MIXED LIGAND COORDINATION COMPOUNDS OF CALCIUM ACETATE WITH SOME ORGANIC LIGANDS - Nurillayev Bunyodjon Khikmatilla ugli; Ismailov Akmal Aslanbekovich; Fayziyeva Aziza Komil kizi; Akhrorova Durdona Tulkin kizi; Turakulov Jakhongir Ulugbekovich (American Journals Publishing, 2023)
Mixed-ligand coordination compounds of calcium acetate have been synthesized. The composition, identity, methods of coordination of acetate groups, molecules of formamide, acetamide, carbamide, thiocarbamide have been established, and the thermal behavior of the obtained complexes has been studied.